The Cambridge introduction to Marcel Proust - Watt, Adam A. (Adam Andrew), 1979- (Cambridge University Press, 2011)
"Proust's A la recherche du temps perdu (In Search of Lost Time, 1913-27) changed the course of modern narrative fiction. This Introduction provides an account of Proust's life, the socio-historical and cultural contexts of his work and an assessment of his early works. At its core is a volume-by-volume study of In Search of Lost Time, which attends to its remarkable superstructure, as well as to individual images and the intricacies of Proust's finely-stitched prose. The book reaches beyond stale commonplaces of madeleines and memory, alerting readers to Proust's verbal virtuosity, his preoccupations with the fleeting and the unforeseeable, with desire, jealousy and the nature of reality. Lively, informative chapters on Proust criticism and the work's afterlives in contemporary culture provide a multitude of paths to follow. The book charges readers with the energy and confidence to move beyond anecdote and hearsay and to read Proust's novel for themselves"--